Stakeholder informed development of the Emotion Awareness and Skills Enhancement team–based program (EASE-Teams). (April 2022) - Beck, Kelly B; Northrup, Jessie B; Breitenfeldt, Kaitlyn E; Porton, Shannon; Day, Taylor N; MacKenzie, Kristen T; Conner, Caitlin M; Mazefsky, Carla A
Emotion dysregulation (ED) underlies psychiatric symptoms and impedes adaptive responses in autistic individuals. The Emotion Awareness and Skills Enhancement (EASE) program was the first mindfulness-based intervention designed to target emotion dysregulation in autistic adolescents (12–17 years old). This project partnered with stakeholders to adapt EASE for autistic adolescents and adults with co-occurring intellectual disability and autistic elementary-aged children, groups who often benefit from caregiver support in treatment. Over three adaptation phases, we: (1) elicited stakeholder and expert feedback to adapt the original EASE program for autistic individuals with intellectual disability; (2) redesigned the adapted manual and expanded the target age range following a small "micro-trial" with a sample of autistic adolescents and adults with intellectual disability ( n = 6); and (3) demonstrated feasibility and acceptability of a caregiver-client team-based approach (EASE-Teams) in a sample of 10 autistic individuals with and without intellectual disability (ages 7–25) and their caregivers. EASE-Teams was both acceptable and helpful to families. Significant improvements were noted in participant emotion dysregulation, psychiatric symptoms, and caregiver stress from their child's dysregulation. Findings suggest that EASE-Teams may be appropriate for heterogeneous developmental and cognitive needs. Future research to establish efficacy and refine EASE-Teams with community providers is warranted. Lay abstract: Emotion dysregulation (ED) impacts mental health symptoms and well-being in autistic individuals. In prior work, we developed the Emotion Awareness and Skills Enhancement (EASE) to improve emotion dysregulation with autistic adolescents (aged 12–17). The study team partnered with autistic individuals, their caregivers, and expert clinicians to adapt EASE for autistic adolescents and adults with co-occurring intellectual disability and autistic elementary-aged children, groups that often benefit from caregiver support in treatment. In three phases, we (1) gathered caregiver and expert feedback to adapt the original EASE program for autistic adults with intellectual disability, (2) revised the treatment after using it with six autistic adults with intellectual disability, and (3) tested the newly developed caregiver–client team-based treatment, called EASE-Teams, in a small group of 10 autistic individuals with and without intellectual disability (aged 7–25). Families found EASE-Teams to be acceptable and helpful. We found improvements in emotion dysregulation and mental health symptoms for autistic participants. Caregivers reported less stress from their child's dysregulation after participating. These results show that EASE-Teams can be appropriate for different developmental and cognitive needs. Future studies will need to test the benefits of the treatment in community clinics.